SISTEM PEMANTAUAN SUHU DEMAM BERDARAH SECARA OTOMATIS DAN REALTIME BERBASIS LabVIEW 7.1 - Qomariyah, Siti; Rahayu, Rahayu; Dharmala, Budi (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
Bodyâs temperature of dengue fever patient in hospital were monitored to draw its development phase where believes obeys the so-called saddle back pattern. It is therefore the aim of this study to build a monitoring system of bodyâs temperature of dengue fever patient atomatically and in a realtime manner. The built system uses an IC LM35 as a main temperature sensor equipped by a voltage regulator, a DAQ interface unit and package program of LabVIEW 7.1 as an operational system basis as well as a visual display unit. After sets of bodyâs temperature measurements we found a transfer function as V = 0.01Î¸ â 0.05. This transfer function were then used as main input to acquire the calibration function where to be found as Î¸ = 79.69 V â 7.81 and considered as the sensor characteristic. Later, such calibration function being inputed into formula XI box within LabVIEW 7.1 component diagram blocks which runs the whole monitoring system. Monitored bodyâs temperature was nicely plotted graphically onto panel front of LabVIEW7.1 and to be set well-operated within range 30 to 40oC. Respond stability of such sensor to be found as 99.8% at the temperature measurement of 35.1oC. Keywords: LM35, The body temperature, LabVIEW7.1